Self-efficacy of the individual: a psychological discourse (Actual Problems of Psychology in Educational Institutions, 2023)
The article is devoted to the problem of self-efficacy, which isparticularly acute in our country today. The importance of its research inboth theoretical and practical-pragmatic aspects is indicated. An attemptwas made to analyze traditional approaches to the problem in both domesticand foreign psychology. A theoretical overview of some traditional andmodern concepts of self-efficacy is presented, and various definitive positionsregarding the psychological content of the concept are considered. It wasfound that self-efficacy is a repeatedly verified experience of productiveself-realization; a unique and generalized quality in which various mentalelements are integrated, including motivation, cognitive components, asense of confidence, attitude to success, etc. Self-efficacy is consideredas a process and a result of self-creation of a person, an indicator of aperson’s psychological maturity and competence. The connection of selfefficacy with the concept of “I”, values, meanings, abilities and strategies ofproactive behavior is emphasized. The role of self-efficacy in the structureof stress resistance is emphasized. Prospects for further scientific researchare outlined. It is noted about the need to create a coherent theoreticalmodel of the study of the phenomenon in the personal paradigm.
Keywords: self-efficacy; productivity; resource; experience; self-realization